Prediktabilitas Return Saham Jangka Pendek di Bursa Efek Indonesia - , Leo Willyanto, ST ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The concept of market efficiency has been the foundation of much both empirical and theoretical research in financial economics. The concept that was early researched by Fama (1970) and other scholar has moved other kind of research. There are some that view the market efficiency concept from the pros and some from the cons. This research is aimed to test wether or not the short term stock return predictability exist. This predictability will determine the market is efficient or not through the observation of monthly stock return. Previous research by Jegadessh (1990) investigates the various aspect of return predictability by analizing the serial correlation of individual monthly stock return and found that return have a predictable behavior. The research in Indonesian Stock Exchange is done by testing a hypothesis which is trying to prove the predictability of stock return. This research will test the influence of historical stock return to the current stock return with a tool of regression model and eventually shows a predictable pattern of stock return. The result of this research indicates that the historical stock return had a positive influence to the current stock return in short term period. However, if observed from the pattern of significant regression coefficient, stock return lags moves randomly and shows no consistency on the pattern and the influence to current stock return.